Research on the Knowledge Sharing Theory Constructed by the Global Higher Design Education Community - Xiao, Yao; Sun, Ying (Pinnacle Academic Press Proceedings Series, 2026)
Driven by globalization and digitalization, higher design education faces persistent challenges of uneven resource distribution, fragmented collaboration, and differentiated development levels across regions. Building a global higher design education community has therefore become a key strategy for integrating high-quality resources and promoting coordinated, sustainable development. Knowledge sharing theory provides the core conceptual and methodological support for ensuring the effective operation of such a community. This paper adopts literature research, case analysis, and systematic induction to explore the theoretical connotation, structural elements, and practical mechanisms of knowledge sharing in the context of global higher design education. It examines the roles, motivations, and capabilities of major actors, including teachers, students, and industry experts, and clarifies the types, characteristics, and sharing barriers of design education knowledge. Furthermore, it analyzes how institutional arrangements, cultural norms, and technological environments jointly shape knowledge flows and collaboration patterns. On this basis, the study proposes three practical paths: constructing incentive and trust-based mechanisms, coordinating physical and digital platforms for interaction, and cultivating an open, shared culture that supports long-term cooperation. Typical cases are used to summarize successful experiences and reveal existing problems in current practice. The findings enrich the theoretical system of knowledge sharing in design education and offer operational strategies for constructing a global higher design education community, contributing to the cultivation of high-quality talents with international vision, innovation capability, and cross-cultural communication competence.